1990
DOI: 10.1002/bjs.1800770209
|View full text |Cite
|
Sign up to set email alerts
|

Sutured posterior abdominal rectopexy with sigmoidectomy compared with Marlex® rectopexy for rectal prolapse

Abstract: Two treatment policies for rectal prolapse were prospectively assessed between April 1986 and January 1989. Sixteen patients had a Marlex mesh posterior rectopexy alone and 13 underwent a sigmoidectomy combined with a sutured posterior rectopexy. Preoperative and post-operative assessment included manometry, a saline infusion test and video-proctography. Hospital stay, control of prolapse and complications were comparable in both groups. Restoration of continence occurred in nine of the 12 incontinent patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1
5

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 12 publications
6
53
1
5
Order By: Relevance
“…In the postoperative period, 9 (60%) of these 16 patients improved as regards their constipation. Constipation is a common problem after rectopexy, particularly so after posterior mesh rectopexy [24]. Studies have demonstrated that constipation increased from 10-47% and suggested a link with denervating the left colon and rectum with possible kinking at the recto-sigmoid junction by a redundant, unresected sigmoid colon prolapsing into the pouch of Douglas [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the postoperative period, 9 (60%) of these 16 patients improved as regards their constipation. Constipation is a common problem after rectopexy, particularly so after posterior mesh rectopexy [24]. Studies have demonstrated that constipation increased from 10-47% and suggested a link with denervating the left colon and rectum with possible kinking at the recto-sigmoid junction by a redundant, unresected sigmoid colon prolapsing into the pouch of Douglas [24].…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is a common problem after rectopexy, particularly so after posterior mesh rectopexy [24]. Studies have demonstrated that constipation increased from 10-47% and suggested a link with denervating the left colon and rectum with possible kinking at the recto-sigmoid junction by a redundant, unresected sigmoid colon prolapsing into the pouch of Douglas [24]. This may be specially so because the lateral ligaments containing the parasympathetic inflow to the left colon may be cut during mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen percent of patients experience constipation for the first time following rectopexy, and at least 50 % of those who are constipated preoperatively are made worse [22]. The addition of sigmoidectomy to the operation was felt to be associated with a lower recurrence rate and improved functional outcome with a minimal increase in morbidity [23,24]. It seems to reduce constipation significantly in those who report this symptom preoperatively in some studies [23,25,26].…”
Section: Constipationmentioning
confidence: 99%